Erythrocyte membrane protein destabilization versus clinical outcome in 160 portuguese hereditary spherocytosis patients - Rocha, Susana (2011)
Hereditary Spherocytosis (HS) is a haemolytic anaemia caused by erythrocyte protein membrane defects - spectrin, ankyrin, band 3 or protein 4.2 - that lead to membrane destabilization. This study aimed to evaluate the prevalence of protein deficiencies and the role of membrane proteins or membrane-linked proteins in membrane disturbance and in HS clinical outcome. A total of 215 Portuguese individuals were studied - 203 from 71 families plus 12 individual unrelated subjects; 160 of them were diagnosed with HS. They were classified as presenting mild, moderate or severe forms of HS according to the degree of haemolytic anaemia. Standardized electrophoretic erythrocyte membrane protein analysis was used to identify and quantify protein deficiencies. Band 3 and ankyrin were found to account for the majority of the erythrocyte protein defects underlying HS. Increasing isolated protein deficiency or increasing imbalance between combined protein deficiencies seemed to underlie HS severity, by increasing membrane destabilization. There was an increased membrane linkage of the cytosolic proteins, glyceraldehyde-3-phosphate dehydrogenase and peroxiredoxin 2, and of denatured haemoglobin, suggesting that this linkage could interfere with membrane structure. Our data suggest that the quantification and the analysis of RBC membrane proteins may be helpful in predicting the clinical outcome of HS.